Immune Suppressive Extracellular Vesicle Proteins of Leptopilina heterotoma Are Encoded in the Wasp Genome. Issue 1 (1st January 2020) - Wey, Brian; Heavner, Mary Ellen; Wittmeyer, Kameron T; Briese, Thomas; Hopper, Keith R; Govind, Shubha
Abstract: Leptopilina heterotoma are obligate parasitoid wasps that develop in the body of their Drosophila hosts. During oviposition, female wasps introduce venom into the larval hosts' body cavity. The venom contains discrete, 300 nm-wide, mixed-strategy extracellular vesicles (MSEVs), until recently referred to as virus-like particles. While the crucial immune suppressive functions of L. heterotoma MSEVs have remained undisputed, their biotic nature and origin still remain controversial. In recent proteomics analyses of L. heterotoma MSEVs, we identified 161 proteins in three classes: conserved eukaryotic proteins, infection and immunity related proteins, and proteins without clear annotation. Here we report 246 additional proteins from the L. heterotoma MSEV proteome. An enrichment analysis of the entire proteome supports vesicular nature of these structures. Sequences for more than 90% of these proteins are present in the whole-body transcriptome. Sequencing and de novo assembly of the 460 Mb-sized L. heterotoma genome revealed 90% of MSEV proteins have coding regions within the genomic scaffolds. Altogether, these results explain the stable association of MSEVs with their wasps, and like other wasp structures, their vertical inheritance. While our results do not rule out a viral origin of MSEVs, they suggest that a similar strategy for co-opting cellular machinery for immune suppression may be shared by other wasps to gain advantage over their hosts. These results are relevant to our understanding of the evolution of figitid and related wasp species.